STRATEGI PEMBELAJARAN GURU DALAM MENINGKATKAN METAKOGNISI MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Khairani, Eka Ulfa; Faizal Chan; Suci Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe teacher strategies in planning, implementing, and evaluating mathematics learning to improve students' metacognitive skills in class V of elementary school. The study used a qualitative approach with a case study method, conducted at SD Negeri 34/I Teratai. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that teachers designed and applied various learning strategies to enhance students' metacognition. These included reflective questioning, collaborative problem-solving, and assessment-based learning. The evaluation involved feedback, reflection, and revision of teaching strategies. This study concluded that a well-structured teaching strategy can effectively improve students' mathematical metacognition skills.